2018
DOI: 10.1007/s00204-018-2295-8
|View full text |Cite
|
Sign up to set email alerts
|

Possible neurotoxicity of the anesthetic propofol: evidence for the inhibition of complex II of the respiratory chain in area CA3 of rat hippocampal slices

Abstract: Propofol is the most frequently used intravenous anesthetic for induction and maintenance of anesthesia. Propofol acts first and formost as a GABAA-agonist, but effects on other neuronal receptors and voltage-gated ion channels have been described. Besides its direct effect on neurotransmission, propofol-dependent impairment of mitochondrial function in neurons has been suggested to be responsible for neurotoxicity and postoperative brain dysfunction. To clarify the potential neurotoxic effect in more detail, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…Pediatric anaesthesiologists are concerned, since it has been proposed that anaesthetic agents may be neurotoxic to the developing brain [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric anaesthesiologists are concerned, since it has been proposed that anaesthetic agents may be neurotoxic to the developing brain [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms by which sevoflurane and desflurane produce such cytotoxicity are yet to be determined, the involvement of Drp1, Fas, and mitochondrial permeability transition pore activation-mediated fission are a few possibilities (Zhang and Xie 2012). Similar mitochondrial impairments have been reported with propofol (Berndt et al 2018;Twaroski et al 2015) and ketamine (Bosnjak et al 2012;Braun et al 2010;Ito et al 2015).…”
Section: Anesthetic Neurotoxicity In Animal and In Vitro Studiesmentioning
confidence: 83%
“…The evidence derived from animal studies is abundant, with initial studies showing that early exposure to isoflurane and nitrous oxide causes neurodegeneration and cognitive deficits in young rats (Jevtovic-Todorovic et al 2003). Since then, multiple GABA agonistic and NMDA antagonistic agents including sevoflurane (Istaphanous et al 2011;Lu et al 2010;Sun et al 2019;Wang et al 2013;Xie et al 2017;Xu et al 2016Xu et al , 2018, isoflurane (Istaphanous et al 2011;Lemkuil et al 2011;Talpos et al 2019;Tao et al 2016;Xu et al 2016Xu et al , 2018Zhang et al 2010;Zhu et al 2010), desflurane (Istaphanous et al 2011Tao et al 2016;Xu et al 2016), nitrous oxide (Jevtovic-Todorovic and Carter 2005;Jevtović-Todorović et al 1998;Talpos et al 2019), propofol (Berndt et al 2018;Bosnjak et al 2016;Pearn et al 2012;Xu et al 2018), and ketamine (Brambrink et al 2012a;Ito et al 2015;Slikker et al 2007) have been found to compromise neuronal health, synaptic network assembly, and learning and memory in both young and aged brains in a number of species ranging from invertebrates, to rodents, to nonhuman primates (Slikker et al 2007;Talpos et al 2019). Evidence of neurotoxicity in young nonhuman primates stands out because of its relevancy to humans.…”
Section: Anesthetic Neurotoxicity In Animal and In Vitro Studiesmentioning
confidence: 99%
“…Propofol is a commonly used intravenous anesthetic agent for gastrointestinal endoscopy may lead to cognitive impairment [2] . Mounting evidence from experimental models has demonstrated that propofol could induce a similar neurotoxic effect [9][10][11] . Allampati et al [12] have reported that in humans,cognitive exibility returns to baseline within 30-45 min after propofol sedation despite delayed return of psychomotor speed and reaction time.…”
Section: Discussionmentioning
confidence: 99%